Evaluating the Role of Participation in Different Design Phases for More Inclusive Housing - DEMİREL, Abdullah Eren; ALHANOUSH ALKHALAF, Mohammad Nasim (İDEALKENT, 2022)
Urban growth and population increase have been major driving forces for cities, combined with an expanding heterogeneous sociocultural structure. The growing trends in urbanization pose massive challenges of inequalities and exclusions, primarily observed in housing. While housing was initially a sociocultural product involving users, it has transformed into a more standardized and financialized entity in the twentieth century, resulting in the abstraction of users from the production process. Against these exclusionary housing trends, it is the role of designers to redefine the place of users in housing for more inclusive results. So, this paper aims to investigate the potential of participatory approaches in housing to achieve more inclusive outcomes. Accordingly, accumulated knowledge on participation in housing starting in the 1960s is chronologically and interrelatedly discussed and mapped through prominent publications. Then, the benefits of specific participatory approaches in the inclusivity of housing are evaluated regarding three design phases to form a framework for future practices: i) design/predesign, ii) implementation, and iii) (post) occupancy. The study showed that participatory approaches at various phases and levels contribute to creating inclusive housing by increasing users’ representation in decision-making, demystifying professional tools, and allowing alternative and dynamic appropriation of living. Kentsel büyüme ve nüfus artışı, genişleyen ve heterojen sosyo-kültürel yapıyla birlikte şehirler için temel itici güçler olmuştur. Kentleşmedeki artan eğilimler, özellikle konut alanında gözlemlenen büyük eşitsizlik ve dışlanmayı da ortaya çıkarmaktadır. Konut, eskiden kullanıcılar tarafından oluşan sosyokültürel bir ürünken, yirminci yüzyılda daha standartlaştırılmış ve finansallaşmış bir varlığa dönüşmüş ve kullanıcılar üretim sürecinden soyutlanmıştır. Bu dışlayıcı konut eğilimlerine karşı, daha kapsayıcı sonuçlar için kullanıcıların konut üretimindeki yerini yeniden tanımlamak tasarımcıların görevidir. Dolayısıyla bu makale, daha kapsayıcı sonuçlar elde etmek için konutta katılımcı yaklaşımların potansiyelini araştırmayı amaçlamaktadır. Buna göre, 1960'lardan başlayarak konut katılımına ilişkin biriken bilgi, önde gelen yayınlar aracılığıyla kronolojik ve birbiriyle ilişkili olarak tartışılmakta ve haritalanmaktadır. Sonrasında, konutun kapsayıcılığına yönelik belirli katılımcı yaklaşımların faydaları, gelecekteki uygulamalar için bir çerçeve oluşturmak üzere üç tasarım aşamasına göre değerlendirilir: i) tasarım/tasarım öncesi, ii) uygulama ve iii) kullanım(sonrası). Çalışma, çeşitli aşamalarda ve seviyelerde katılımcı yaklaşımların, kullanıcıların karar verme süreçlerinde temsilini artırarak, katılımı kolaylaştırma yolunda profesyonel araçları anlaşılır kılarak ve inşaat ve kullanım sırasında çevrelerin dönüştürülmesine izin vererek kapsayıcı konut yaratılmasına katkıda bulunduğunu göstermiştir.